Antibacterial Effect of Bacteriocin Isolated From Lactobacillus Plantarum ATCC 8014 on Postoperative Infection of Mandibular Fracture In Vivo. Issue 3 (May 2017) - Fu, Tao; Liu, Yan-Ming
Abstract : Objective: The primary objective of this study was to verify the effects of bacteriocin in treatment of postoperative infection of mandibular fracture in vivo. Methods: Eighty-two mice were inoculated intravenously with staphylococcal suspensions. Bacterial cultures were obtained from implants. Blood samples were collected at 1, 2, 4, 6, and 8 hours after the injection of bacteriocins. Results: Bacteriocins have significant inhibitory effects on Staphylococcus aureus ( P < 0.05) and there are significant differences interleukin (IL)-8 and IL-10 in serum ( P < 0.05). Conclusions: Bacteriocin isolated from L plantarum may be one of promising ways to control postoperative infection of mandibular fracture in vivo.